2015
DOI: 10.15252/embj.201490786
|View full text |Cite
|
Sign up to set email alerts
|

Molecular profiling of CD 8 T cells in autochthonous melanoma identifies Maf as driver of exhaustion

Abstract: T cells infiltrating neoplasms express surface molecules typical of chronically virus-stimulated T cells, often termed "exhausted" T cells. We compared the transcriptome of "exhausted" CD8 T cells infiltrating autochthonous melanomas to those of naïve and acutely stimulated CD8 T cells. Despite strong similarities between transcriptional signatures of tumor-and virus-induced exhausted CD8 T cells, notable differences appeared. Among transcriptional regulators, Nr4a2 and Maf were highly overexpressed in tumor-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
114
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(123 citation statements)
references
References 66 publications
3
114
0
Order By: Relevance
“…All comparison populations and statistics used to generate gene sets have been published (17, 31-34). For gene sets corresponding to human data, gene symbols were converted to mouse gene symbols by the Database for Annotation, Visualization and Integrated Discovery (DAVID) version 6.7 (35, 36), and gene symbols were manually verified to contain the gene symbol identifier(s) corresponding to our microarray Probe Set ID’s.…”
Section: Methodsmentioning
confidence: 99%
“…All comparison populations and statistics used to generate gene sets have been published (17, 31-34). For gene sets corresponding to human data, gene symbols were converted to mouse gene symbols by the Database for Annotation, Visualization and Integrated Discovery (DAVID) version 6.7 (35, 36), and gene symbols were manually verified to contain the gene symbol identifier(s) corresponding to our microarray Probe Set ID’s.…”
Section: Methodsmentioning
confidence: 99%
“…The loss of CD4 + T cell help, particularly in the form of IL-21 [46] and signaling downstream of the immunosuppressive cytokines, IL-10 and TGF-β, were shown to promote T cell dysfunction [7, 8]. More recently, IL-6 signaling, alone or in combination with TGF-β, was shown to induce the transcription factor Maf, a potential driver of CD8 + T cell dysfunction in tumor [9]; however the role of IL-6 in driving dysfunctional phenotype in vivo was not addressed. That Maf is driven by Stat3 signaling [10] further raises the possibility that other cytokines that activate Stat3 may also play a role in regulating T cell dysfunction.…”
Section: T Cell Dysfunctionmentioning
confidence: 99%
“…Several gene signatures (see glossary) based on analyses of populations of dysfunctional CD8 + T cells from cancer and chronic viral infections have been published [9, 2125]. These signatures have shown that there is great similarity between virus- and cancer-associated CD8 + T cell dysfunction and have greatly advanced our understanding of factors that contribute to dysfunctional phenotype.…”
Section: Molecular Signatures Of T Cell Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our recent study, 3 we took advantage of a mouse model of induced melanoma based on conditional deletion of tumor suppressor genes with concomitant expression of a natural mouse tumor antigen (TiRP mice). In this model, tumorintrinsic factors control the development of aggressive tumors and their expression of an inflammatory/immunosuppressive program.…”
mentioning
confidence: 99%